I'm assuming 43 is actually 4/3
see what number the previous term must be multiplied by to get the next term
4 *something = 12, 12*something=36
common ratio is 3
Answer:
Sequence: 13, 20, 27
Rule: Tn = 7n + 6
Step-by-step explanation:
The 3 other numbers that can form an arithmetic progression is 13, 20, 27...
The nth term of an arithmetic progression is expressed as;
Tn = a + (n-1)d
a is the first term = 13
n is the number of terms
d is the common difference = 20 - 13 = 27 - 20
d = 7
Substitute
Tn = 13 + (n-1)(7)
Tn = 13 + 7n - 7
Tn = 7n+13-7
Tn = 7n + 6
This gives the required rule
Answer:
11 dimes equals 110
Step-by-step explanation:
so you have 3.45 cents.
Answer:
s=p−(p⋅d) . 0.75p
Step-by-step explanation:
Answer:
![\frac{3 + \sqrt{3x} }{3 - x}](https://tex.z-dn.net/?f=%5Cfrac%7B3%20%2B%20%5Csqrt%7B3x%7D%20%7D%7B3%20-%20x%7D)
Step-by-step explanation:
You can use the work they gave you and continue from there:
![\frac{\sqrt{3}(\sqrt{3}) + \sqrt{3}(\sqrt{x}) }{(\sqrt{3}) ^{2} - (\sqrt{x} )^{2} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B3%7D%28%5Csqrt%7B3%7D%29%20%2B%20%5Csqrt%7B3%7D%28%5Csqrt%7Bx%7D%29%20%20%7D%7B%28%5Csqrt%7B3%7D%29%20%5E%7B2%7D%20-%20%28%5Csqrt%7Bx%7D%20%29%5E%7B2%7D%20%7D)
First, simplify the numerator:
![\frac{3 + \sqrt{3x} }{(\sqrt{3}) ^{2} - (\sqrt{x}) ^{2} }](https://tex.z-dn.net/?f=%5Cfrac%7B3%20%2B%20%5Csqrt%7B3x%7D%20%7D%7B%28%5Csqrt%7B3%7D%29%20%5E%7B2%7D%20-%20%28%5Csqrt%7Bx%7D%29%20%5E%7B2%7D%20%7D)
Finally, simplify the denominator:
![\frac{3 + \sqrt{3x} }{3 - x}](https://tex.z-dn.net/?f=%5Cfrac%7B3%20%2B%20%5Csqrt%7B3x%7D%20%7D%7B3%20-%20x%7D)